The first Similifaveoloolithidae (Wormoolithus luxiensis oogen. et oosp. nov.) from the Upper Cretaceous of Jiangxi Province, China. (4th May 2021) - Zhu, Xufeng; Fang, Kaiyong; Wang, Qiang; Deng, Li; Liu, Yuchun; Wen, Jun; Wang, Xiaolin; Wang, Xuri
ABSTRACT: This study describes a new member of Similifaveoloolithidae from the Upper Cretaceous Zhoutian Formation of Jiangxi, China. The new ootaxon, Wormoolithus luxiensis oogen. et oosp. nov., is erected based on eggs collected from a partial clutch and represents the second oogenera of Similifaveoloolithidae. Wormoolithus shares some unique features with Similifaveoloolithus such as irregularly branched eggshell units, irregular cavities in the inner part of eggshell that are worm-like in tangential view and oblique pore canals in the outer part of the eggshell that show honeycomb-like structure in tangential view. And it is distinguished from the latter by longer polar axis and equatorial diameter and absence of compact layer. Although the clutch is not complete, the preserved parts show that the eggs are closely stacked in the nest. In addition, clay minerals that occur in pores and a high estimated water vapour conductance indicate a humid burial nest microenvironment.